FTKPM UMPSA graduates sought after by employers - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 17 May 2024 – Graduates of the Faculty of Manufacturing and Mechatronics Engineering Technology (FTKPM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) have good job opportunities in various engineering sectors including manufacturing, oil and gas, services, research and various other engineering sectors.